Kentucky's Frontier Highway : Historical Landscapes along the Maysville Road - Raitz, Karl B. (Book collections on Project MUSE., 2012)
Kentucky's Frontier Highway reveals the astounding history of the Maysville Road, a route that served as a theater of local settlement, an engine of economic development, a symbol of the national political process, and an essential part of the Underground Railroad. Authors Karl Raitz and Nancy O'Malley chart its transformation from an ancient footpath used by Native Americans and early settlers to a central highway, examining the effect that its development had on the evolution of transportation technology as well as the usage and abandonment of other thoroughfares, and illustrating how this historic road shaped the wider American landscape.